(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
In this article was discussed, the proverb, which is one of the oldest examples of folklore, differs from other genres by its short, concise, figurative and deep meaning. Proverbs show the ancient and rich spirituality of each nation. Moreover, phraseological units of English and Uzbek languages and a comparative study of the conceptual layers describing the social, physiological and psychological nature of female and male concepts in this article, and the disclosure of their similarities and differences were mentioned in this article.